MODERN TENDENCIES OF DEVELOPMENT OF INNOVATIVE PROCESSES IN RUSSIAN ECONOMY - Lev Ushvitskiy; Anna Ter-Grigor'yants; Alexey Rebiy (Вестник Северо-Кавказского федерального университета, 2022)
The results of the economic analysis of the dynamics of innovation processes in Russia on the basis of an assessment of the elements of the scientific and technical potential of the country and the resulting indicators of its innovation activity, which allowed to highlight the problems of formation andfunctioning of effective national innovation system.